Macrobiotus furciger Murray 1906 - Kaczmarek, Łukasz; Michalczyk, Łukasz; Mcinnes, Sandra J. (Zenodo, 2015)
162. Macrobiotus furciger Murray, 1906b sensu lato [T] Macrobiotus furcatus Murray (Richters 1908a, Ramazzotti 1964b) M. furciger ( andersoni ?) (Mihelčič 1972) M. furciger Murray, 1907 (Claps & Rossi 1981) Terra typica : South Orkney Islands (Southern Ocean) Argentina: • 41°11′S, 71°49′W; 1,800 m asl : Rio Negro Province, Nahuel Huapi National Park, Monte Tronador, semi-wet, lichens on rocks, semi-wet, mosses on tree and mosses on soil (3 samples). Claps & Rossi (1981) • 42°42′S, 70°30′W; 500 m asl : Chubut Province, Gualjaina, semi-wet, mosses on rocks in the mountains. Claps & Rossi (1981) • 54°48′S, 68°18′W; 50 m asl : Type Locality : Tierra del Fuego Province, Isla Grande de Tierra del Fuego, Ushuaia. Richters (1908a) • 54°52′S, 67°25′W: 0 m asl : Tierra del Fuego Province, Harberton Bay. Richters (1908a) • Undefined localities cited according Mihelčič (1967), shaded and wet lichens on tree and dry mosses and lichens on soil in full sun (2 samples). Mihelčič (1972) Chile: • 42°37′S, 73°49′W; 50–100 m asl : Region X Los Lagos (Región de Los Lagos), Chiloé Island, mosses (3 samples). Ramazzotti (1964b) • 55°04′S, 67°37′W: Undefined locality in Region XII Magallanes (Región de Magallanes y de la Antártica Chilena), Navarino Island. Richters (1908a) Record numbers: Argentina: 5, Chile: 2; total: 7. Remarks: Species of the Macrobiotus furciger -group are reported from localities throughout the world but many require verification according to modern literature (for more details see Binda & Rebecchi 1992 and Binda et al. 2005). Binda et al. (2005), reduced the range of Macrobiotus furciger sensu stricto to the maritime Antarctic and sub-Antarctic South Georgia, suggesting the South American records require confirmation. Published as part of Kaczmarek, Łukasz, Michalczyk, Łukasz & Mcinnes, Sandra J., 2015, Annotated zoogeography of non-marine Tardigrada. Part II: South America, pp. 1-107 in Zootaxa 3923 (1) on page 65, DOI:10.11646/zootaxa.3923.1.1, http://zenodo.org/record/241936